The Relationship Between the Knowledge Level of Pregnant Women and The Incidence of High-Risk Pregnancies at Bpm Salabiah, Lhokseumawe City - Myrna Lestari; Fatiyani; Elvieta; Yenni Fitri Wahyuni (International Journal of Health Engineering and Technology, 2025)
This study aims to determine the relationship between pregnant women’s knowledge levels and the incidence of high-risk pregnancy at BPM Salabiah, Lhokseumawe City. Pregnancy is a crucial period in a woman’s life, and limited knowledge about maternal health often contributes to complications that may lead to high-risk conditions. This research employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 63 pregnant women selected using purposive sampling techniques. Data were collected through structured questionnaires and analyzed using univariate analysis to describe respondent characteristics, while bivariate analysis with the Chi-Square test was used to identify relationships between variables. The findings revealed that most respondents were aged 20–35 years (55.6%), the majority were housewives (79.4%), and most were primigravida (43.8%). Furthermore, it was found that pregnant women with low knowledge levels tended to experience a higher incidence of high-risk pregnancy. The statistical analysis confirmed this relationship, with a significant p-value of 0.000 (p < 0.05), indicating that knowledge level plays a vital role in determining maternal health outcomes. These results highlight the importance of providing adequate information and continuous counseling to pregnant women regarding prenatal care, nutrition, and early detection of pregnancy complications. Strengthening health education programs at the community level and encouraging active participation of health workers can help reduce high-risk pregnancies. Therefore, this study recommends an integrated approach involving healthcare providers, families, and communities to improve maternal knowledge and ensure safer pregnancy outcomes.